2005
DOI: 10.1111/j.1471-6712.2005.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with chronic obstructive pulmonary disease: Part I. Struggling with meal‐related situations: experiences among persons with COPD

Abstract: Reduced nutritional intake with low and decreased body weight can be a component of normal ageing. There is, however, also a greater risk for reduced nutritional intake within certain diagnoses, especially for chronic diseases. Malnutrition in chronic obstructive pulmonary disease (COPD) is caused by many factors. The relationship between COPD and low values of body mass index (BMI) is a known independent risk for mortality. For optimal support and care with special focus on nutritional status and intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 40 publications
2
83
0
1
Order By: Relevance
“…Further, it was shown in a study by Odencrants, Ehnfors and Grobe (2005) that solitude was sometimes chosen actively as some elderly people felt as if they were being observed while they were eating and found it hard to follow new socio-cultural codes (Odencrants, Ehnfors, & Grobe, 2005). Another study showed that elderly people chose to eat alone because they do not feel comfortable having company during meals they had not chosen freely, for example in the presence of assistant nurses (Leppänen, 2008).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Further, it was shown in a study by Odencrants, Ehnfors and Grobe (2005) that solitude was sometimes chosen actively as some elderly people felt as if they were being observed while they were eating and found it hard to follow new socio-cultural codes (Odencrants, Ehnfors, & Grobe, 2005). Another study showed that elderly people chose to eat alone because they do not feel comfortable having company during meals they had not chosen freely, for example in the presence of assistant nurses (Leppänen, 2008).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…2 Comorbidities-for example, osteoporosis, depression, ischemic heart disease, diabetes and so on-are common in COPD patients 3 and the general symptom distress is high. 4,5 Many of the common symptoms and problems experienced by COPD patients are likely to negatively affect a patient´s will or ability to eat and have been shown to be common in patients with COPD [6][7][8] and even more so among malnourished patients. 8 Multiple nutrition impact symptoms (NIS) are also common 6 and has been associated with a lower energy intake compared with patients without NIS.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal infections or a dry mouth resulting from the use of puffers can make chewing painful. Coughing before or during meals can tire the person and reduce the focus on the meal, making food a real challenge during exacerbations (Odencrants et al, 2005). Keith (73 yrs) defended his poor eating to his wife Marcia, "Do you want me to eat or do you want me to breathe?…”
Section: Losing Control Of the Body's Taken-for-granted Functionsmentioning
confidence: 99%
“…People experience bloating, feel full before finishing meals and are often embarrassed by the food left on their plate. They report having their intake watched during mealtimes by family members and experienced feelings of failure, anger or sadness when they are not able to eat (Odencrants et al, 2005).…”
Section: Losing Control Of the Body's Taken-for-granted Functionsmentioning
confidence: 99%
See 1 more Smart Citation